Mangroves in Gujarat on Path of Recovery - a Success Story - Singh, H. S. (Indian Forester, 2001)
Coastal wetlands cover largest area in Gujarat State, which accounts for 62.3% of total coastal wetlands of the country. Vast saline mudflats of the Rann of Kutch, the two Gulfs, coral reefs and Mangroves are important wetlands that cover exceptionally large area. Mangroves in the Gulf of Kutch degraded consistently as result of cutting, grazing and lopping but scenario changed after implementation of afforestation and conservation measures. Due to destruction of old Mangrove setting almost everywhere in Gujarat, some of the species exterminated and at present 8 species grow against total 11 species recorded in the past. Inland Mangroves at Shravan Kavadia, covering an area less than a hectare near Bhuj in Kutch District on the fringe of Banni in arid environment is nature’s wonder and its survival is matter of scientific investigation. Avicennia marina is dominant species in the Mangroves of Gujarat. Mangrove cover increased consistently from 397 km2 in 1991 to about 991 km2 in 1997 due to effort of afforestation and conservation after severe drought in 1987. As per the reports, over 95% of Mangroves occur in the Gulf of Kutch. Till year 1998, the Gujarat Forest Department afforested an area of about 13200 ha. As per an estimate, about 600-700 km2 area of the barren mudflat in intertidal zone, mainly located in the two Gulfs, is potential area suitable for Mangrove regeneration. In order to expand the existing Mangrove cover from about 1000 km2 to about 1600 km2 in future requires a planted strategy of regeneration.